The existance of target capital structure on Indonesian firms. A dynamic approach - Haron, Razali (2014)
Very limited studies have been done on the capital structure of Indonesian firms emphasizing on the existence of target capital structure and the affecting determinants and also the speed of adjustment to target leverage. Thus, this study aims to investigate these issues among the firms in Indonesia by using a dynamic model. This study finds that Indonesian firms do employ target capital structure which is influenced by certain firm characteristics like profitability, business risk, firm size and liquidity in their capital structure and they also time their security issuance. Being deviated from target from time to time these firms partially adjust indicating a support for the dynamic trade-off theory. There are also influences of the pecking order and the market timing theories in the capital structure decisions of these firms. This study contributes to the literature by offering insights of the capital structure practice and the adjustment speed to target capital structure of firms in Indonesia and fill the gap in the literature.